2003
DOI: 10.1210/me.2002-0379
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Androgen Receptor Action by Deoxyribonucleic Acid Response Elements

Abstract: In addition to the steroid response elements (SREs), which are recognized by several steroid receptors, a second class of DNA elements exhibiting selectivity for the androgen receptor (AR) and named androgen response elements (AREs) has been identified. Here we provide evidence for the differential role of these element classes in modulating AR function. AR complexes attached to response elements representative of each class were purified. Limited protease digests of ARE- or SRE-bound AR complexes led to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Androgen-dependent expression is conferred by the four AREs in region II (Barbulescu et al 2001, Geserick et al 2003, Bhardwaj et al 2008. These AREs also contribute to the tissue-and cell type-specific expression pattern of the Pp, as recently shown by Bhardwaj et al (2008).…”
Section: The Ppmentioning
confidence: 70%
See 2 more Smart Citations
“…Androgen-dependent expression is conferred by the four AREs in region II (Barbulescu et al 2001, Geserick et al 2003, Bhardwaj et al 2008. These AREs also contribute to the tissue-and cell type-specific expression pattern of the Pp, as recently shown by Bhardwaj et al (2008).…”
Section: The Ppmentioning
confidence: 70%
“…This conclusion comes from several lines of evidence, including: i) Rhox5 mRNA levels (measured with either Rhox5 or Pp-specific probes) are dramatically reduced in animals deficient in the ability to produce LH (the peptide hormone responsible for inducing testosterone production in Leydig cells) as a result of hypophysectomy, chemical treatment, or genetic mutations , 1996c, Maiti et al 1996a, Sutton et al 1998; ii) testosterone reverses the defect in Rhox5 expression caused by loss of LH , Sutton et al 1998; and ix) the Pp possesses four androgen-response elements (AREs), each of which is required for its AR-and androgen-dependent expression in transfected cell lines (Barbulescu et al 2001, Geserick et al 2003, Bhardwaj et al 2008, Faus & Haendler 2008. Together, these studies strongly suggest that the Rhox5 Pp is a direct target of AR in Sertoli cells.…”
Section: The Ppmentioning
confidence: 99%
See 1 more Smart Citation
“…A more resistant conformation was observed for the AR-NTD-DBD bound to DNA in the present study, although no clear differences were observed between selective and non-selective sequences. Recently, Gerserick et al (2003) revealed a change in sensitivity to proteolysis that depended on whether the AR was bound to selective or non-selective elements. Complexes formed with nuclear extracts on selective response elements were less accessible to digestion compared with complexes bound to nonselective elements.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that binding to different AREs indeed induces different conformational changes (Geserick et al 2003). A different DBD conformation might directly or indirectly affect the association with coactivators, as shown for ER (Wood et al 2001, Hall et al 2002.…”
Section: Discussionmentioning
confidence: 95%